APLIKASI INVERSI-AVO UNTUK INTERPRETASI SEISMIK DIBAWAH KETEBALAN TUNING THICKNEES STUDI KASUS LAPANGAN “HD” - Endriasmoro M Siagaan; Agus Setyawan; Oky Irawan Sugiri (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The seismic data has different character, therefore the method used for reservoir characterization of a particular area will not be the same as the other areas. If the coating has a thickness below tuning thickness of the layer, there will be a buildup of wave amplitude. If not recognized can lead to misinterpretation (pitfall). There are several methods that can still interpret the data among other things, methods of seismic inversion and AVO. Both methods are used to characterize the reservoir and determine the rock layers are believed to have potential hydrocarbon accumulation. Seismic inversion methods used to determine the distribution of rock layers below the surface, obtained through this method lithological layers of sandstone that has the potential to be a reservoir. AVO method is the initial method used to determine the gas anomalies and known in this field there is the presence of gas, but in this method can only indicate the presence of gas, by combining these two parameters will be obtained by the distribution of lithology and hydrocarbon clearly. The integration of these two methods shows that although the seismic data below the tuning thickness, can still be interpreted in order to get the reservoar lithological a sandstone layer is enough potential to be explored further. Value inversi Vp/Vs 1,75-1,82Keywords: Inversion, AVO, tuning thickness